2020
DOI: 10.1097/anc.0000000000000825
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Expression, Storage, and Transport by Women Whose Infants Are Inpatients at a Tertiary Neonatal Unit in Melbourne, Australia

Abstract: Background: Expression and storage of mothers' own milk at home and its transportation to hospital neonatal units are a common practice worldwide when newborns are inpatients. Studies assessing adherence to hospital protocols and guidelines for this are not widely published. Purpose: To explore the advice received and practices followed by mothers when expressing, storing, and transporting their milk from home to the hospital, with a substudy exploring the factors related to temperature maintenance of refriger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…However, how the pump is sterilized is a factor that affects the quality of expressed human milk [ 31 ]. Studies have reported that at least 52% of mothers had one or more experiences of ineffective sterilization of breast pump collection kits [ 32 ] and only 54% of mothers correctly followed the information on the refrigeration times of expressed human milk [ 17 ]. This may increase the risk of bacterial contamination of human milk expressed through a breast pump.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, how the pump is sterilized is a factor that affects the quality of expressed human milk [ 31 ]. Studies have reported that at least 52% of mothers had one or more experiences of ineffective sterilization of breast pump collection kits [ 32 ] and only 54% of mothers correctly followed the information on the refrigeration times of expressed human milk [ 17 ]. This may increase the risk of bacterial contamination of human milk expressed through a breast pump.…”
Section: Discussionmentioning
confidence: 99%
“…The main information for 22% of mothers comes from unofficial sources—for example, websites—and these resources may not recommend the same methods as the official guidelines [ 17 ]. The Internet and peer instruction were also other important sources of knowledge for participants in this study, but the scientific nature of the information from these channels was not certain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…/ 2021 / ТОМ 20 / № 6 CURRENT PEDIATRICS / 2021 / V. 20 / № 6 В большинстве развитых стран мира практикуют следующие варианты использования материнского молока в неонатальных стационарах: • кормление свежесцеженным материнским молоком при условии продолжительного/круглосуточного пребывания матери в ОРИТН и достаточном объеме лактации; • кормление материнским молоком, которое матери сцеживают при непродолжительном пребывании в ОРИТН (в дневные часы) и оставляют для ургентного использования или для непродолжительного хранения; • ежедневная транспортировка собранного в домашних условиях в течение суток сцеженного молока (при невозможности пребывания матери в ОРИТН) [67,92,93]. В ОРИТН может быть также использовано замороженное/размороженное материнское молоко; хотя процессы замораживания/размораживания сопряжены с уменьшением нутритивной ценности грудного молока из-за возможной деградации питательных компонентов, прежде всего жира, в результате фотодеградации, окисления на воздухе и оседания на посуде и соединительных трубках при зондовом кормлении [67].…”
Section: две возможности использования грудного молока в оритн: матер...unclassified